2013
DOI: 10.3109/03602532.2012.746363
|View full text |Cite
|
Sign up to set email alerts
|

PXR antagonists and implication in drug metabolism

Abstract: Adopted orphan nuclear receptor (NR), pregnane X receptor (PXR), plays a central role in the regulation of xeno- and endobiotic metabolism. Since the discovery of the functional role of PXR in 1998, there is evolving evidence for the role of PXR agonists in abrogating metabolic pathophysiology (e.g., cholestasis, hypercholesterolemia, and inflammation). However, more recently, it is clear that PXR is also an important mediator of adverse xeno- (e.g., enhances acetaminophen toxicity) and endobiotic (e.g., hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
88
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 115 publications
(168 reference statements)
0
88
0
1
Order By: Relevance
“…In colon cancer cells, expression of wild-type p53 induces apoptosis (Shaw et al, 1992), whereas activation of PXR induces colon tumor growth and malignancy (Wang et al, 2011;Mani et al, 2013;Pondugula and Mani, 2013). In this study, we showed that in colon cancer cell line HCT116, wildtype p53 downregulates PXR activity.…”
Section: Discussionmentioning
confidence: 53%
“…In colon cancer cells, expression of wild-type p53 induces apoptosis (Shaw et al, 1992), whereas activation of PXR induces colon tumor growth and malignancy (Wang et al, 2011;Mani et al, 2013;Pondugula and Mani, 2013). In this study, we showed that in colon cancer cell line HCT116, wildtype p53 downregulates PXR activity.…”
Section: Discussionmentioning
confidence: 53%
“…Similar to the AhR, the pregnane X receptor (PXR) can bind and be activated by a structurally diverse collection of ligands. The results of 3-dimensional protein structure analysis of PXR ligand binding has revealed that the dramatic structural promiscuity of PXR ligands can be explained by the characteristics of its binding pocket, which allows structurally diverse ligands to bind in a variety of different orientations and positions within the PXR LBD (28)(29)(30). By analogy, the structural diversity of AhR ligands may also result from differential interactions of ligands or classes of ligands with different residues within the AhR LBD (1,2).…”
mentioning
confidence: 99%
“…Nuclear receptors are involved in the modulation of hepatocyte priming and proliferation [25]. In addition to FXR, PXR is another nuclear receptor in liver, which is also essential for normal progression of liver regeneration [30,31]. Therefore, we investigated the involvement of PXR in the AB23A-induced liver regeneration promotion.…”
Section: Discussionmentioning
confidence: 99%